Salivary Glucose Level Increases Severity ff Periodontal Condition in Patients with Type 2 DM (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Saliva can be used for early detection of Diabetes Mellitus (DM). The purpose of the study was to determine the relationship between salivary glucose level of patients with type 2 DM on periodontal tissue and to compare it with non DM condition. Observational analysis with cross sectional study was the design used with 40 patients in each group as samples. Periodontal conditions were examined using a dental probe and salivary glucose levels with Eppendorf Ecom 6125 Photometer. The data was analysed statistically with Spearman test to find the relationship between salivary glucose level and periodontal condition and Mann Whitney U Test to compare DM and non DM groups. Cofficient value of Spearman was 0.86, there was a strong correlatiom between salivary glucose level and periodontal condition. Salivary glucose level of DM patients was 8.55 and the control group’s was 1.85 (p=0.02). Higher salivary glucose level would increase severity of periodontal tissue status.